Search Engine –A Demanding Advertising Tool (International Journal of Engineering and Computer Science, 2014)
This paper is mainly focused on approaches and techniques to online promotion on web marketing including search engine optimization, (SEO), online advertisements and new methods of increasing the visitors to a Website. In last decade, the emergence of search engine marketing as one of the fastest growing industries has been observed. Search engine marketing has been categorized as: paid and non-paid. Paid marketing included pay-per-Click (PPC), web page, including the page title, content and keyword density, and come up with a ranking for where to place the results on the pages and paid inclusion while non-paid marketing includes natural SEO and link popularity index. This is still a relatively new market and most of the companies lack in the knowledge or the tools to manage their marketing strategies in order to maximize the return of their investments (ROI). It can be effectively applied to technical aspects in managing paid and non-paid search engine marketing required in the Service Oriented Architecture (SOA) dimension. In this paper an attempt has been made to analyse the following factors: online promotion techniques, search engine optimization, on-page optimization, paid and non paid search marketing, and factors that affect SEO.